Low-Cost Label-Free Electrochemical Aptasensor for Dual Detection of Dengue and Zika Using Fluorine-Doped Tin Oxide Modified with APTES and Gold Nanoparticles - Bachour, Bassam; Sawazaki, Marina Ribeiro Batistuti [UNESP]; Rocha, Ricardo Estéfani França; Guidelli, Éder José; Mulato, Marcelo (American Chemical Society (ACS), 2025)
The incidence of arbovirus infections, such as dengue and zika, has increased dramatically in recent decades, especially in tropical regions and in technologically limited places. The goal of this study is to create an affordable platform for both dengue and zika detection. Fluorine-doped tin oxide-coated substrates were modified with APTES and gold nanoparticles. The modified surfaces were functionalized with the DNA aptamer and 6-mercapto-1-hexanol. Electrochemical impedance spectroscopy was used to characterize and optimize aptasensors' performance using nonstructural protein 1 (NS1) proteins as biomarkers. The biosensor exhibited a limit of detection (LoD) of 0.21 ng/mL for dengue in phosphate-buffered saline (PBS), with a sensitivity of 19.26% per decade. In commercial human serum, the platform showed a signal increase of 2% per decade, a LoD of 0.55 ng/mL, and a sensitivity of 11.87% per decade. For zika detection, the biosensor presented 0.68 ng/mL LoD and a sensitivity of 26.34% per decade in PBS. In this case, the presence of a biological matrix from commercial human serum induced complex interaction with NS1, resulting in nonlinear sensor responses. Although this platform was not able to distinguish between zika and dengue infections, it enables the detection of both in a single test, representing a promising approach for clinical diagnostics.